Optimalisasi Peran dan Fungsi ITB sebagai Pencetak Teknopreneur bagi Kemajuan Bangsa dan Pembangunan Nasional Berkelanjutan - Anggiat BP Sinaga (Fakultas Seni Rupa dan Desain ITB, 2006)
This article suggest that technopreneurship subject should no longer be offered to ITB student as an optional subject but a compulsory one. The reason is that this subject may enable ITB's graduates to be technopreneurs when they graduate. In his opinion, a technopreneur is regarded as a critical success factor in increasing both Growth National Product (GNP). Therefore, their role in resolving Indonesia's current multi dimensional crises and enhancing Indonesia's development will be very significant. The writer also claims that this subject is relevant for ITB's student-who will become engineers and specialists in arts when they graduate-since technopreneurship subject teaches the students how to do business in the field of engineering and art and train the students to acquire technopreneur's qualities such as being critical, innovative, reasonable, positive thinking, risk taking person. Keyword: Technopreneurship subject, technopreneur, technopreneur's qualities, critical success factor.